Current GMP standards for the production of vaccines and antibodies: An overview - Covarrubias, Consuelo E.; Rivera, Thomas A.; Soto, Catalina A.; Deeks, Trevor; Kalergis, Alexis M. (Frontiers in Public Health, 2022)
The manufacture of pharmaceutical products made under good manufacturing practices (GMP) must comply with the guidelines of national regulatory bodies based on international or regional compendia. The existence of this type of regulation allows pharmaceutical laboratories to count on the standardization of high-quality production processes, obtaining a safe product for human use, with a positive impact on public health. In addition, the COVID-19 pandemic highlights the importance of having more and better-distributed manufacturing plants, emphasizing regions such as Latin America. This review shows the most important GMP standards in the world and, in particular, their relevance in the production of vaccines and antibodies.